CARBON ISOTOPIC FRACTIONATION OF CH4 AND CO2 DURING CANISTER DESORPTION OF COAL - Strapoć D.; Schimmelmann A.; Mastalerz M. (My University, 2006)
Canister desorption of coal gas from freshly sampled coal is commonly used for exploratory assessment of the coalbed methane (CBM) potential of a basin or prospect, as well as for the sampling of gas for isotopic determination of the gas origin. Compositional and δ13C isotopic time-series of desorbing CBM and carbon dioxide (CO2) over 3-4 months demonstrate considerable compositional and isotopic shifts over time. Non-stationary chemical and isotopic characteristics are due to differences in diffusivity and adsorbance behavior of gas molecules and must be taken into account when attempting to reproducibly sample coal gases. Off-line gas processing on a vacuum line and on-line GC/MS analyses were performed on coal gas samples from the Springfield and Seelyville Coal Members of the Pennsylvanian age that were cored in the SE Illinois Basin in SW Indiana, USA. The coals cover a narrow range of maturity from 0.54% to 0.64% vitrinite reflectance. Methane initially desorbed faster than CO2, resulting in a 50% increase of the CO 2 content in bulk desorbing gas on the 50th day relative to the first day of desorption. After 50 days of desorption, about 90% of all coal gas was desorbed. Over the same time period, δ13C values of incrementally sampled coal gas increased by 2‰ and 9‰, for CH 4 and CO2, respectively, testifying to the greater retention of 13CH4 and 13CO2 relative to 12CH4 and 12CO2. An isotopic mass balance of the individual, sequentially desorbed and sampled gas amounts yielded weighted mean δ13CCH4 and δ13CCO2 values for characterizing the cumulatively desorbed gas. The overall mean δ13C values were equivalent to δ13C values of gases that desorbed at a time when half of the potentially available gas had been desorbed from coal, corresponding in this study to a time between day 5 and day 12 of canister desorption at 15-18°C. The total expected gas volume and the ~50% midpoint can thus be approximated for a desorbing coal gas sample, based on a dynamic prediction after the first five days of canister desorption. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Pennsylvanian; Paleozoic::Carboniferous::Pennsylvanian; Палеозой::Каменноугольная